Agricultural water management in humid tropics - Varadan, K. M.; Agrobios (India) (Jodhpur : Agrobios (India), 2002)
With special reference to Kerala.
Includes statistical tables.
Includes bibliographical references (p. [126]-132) and index.
Keywords: Irrigation -- India -- Kerala